The safety profile of preoperative administration of heparin for thromboprophylaxis in Chinese patients intended for thoracoscopic major thoracic surgery: a pilot randomized controlled study - Deng, Han-Yu; Shi, Chang-Lin; Li, Gang; Luo, Jun; Wang, Zhi-Qiang; Lin, Yi-Dan; Liu, Lun-Xu; Zhou, Qing-Hua (Journal of Thoracic Disease, 2017)
Background: Patients undergoing major thoracic surgery especially for cancers are at a high risk of perioperative thromboembolism. Current guidelines recommended either heparin sodium (unfractionated heparin) or low-molecular-weight heparin (LMWH) for those patients at high risk of deep vein thrombosis (DVT). However, the rational timing of starting heparin has not yet been well established, because DVT can be caused by not only surgery but also comorbidities as well as prolonged hospital stay, and thoracic surgeons always concerned about heparin-related increased risk of intra- or post-operative bleeding. Therefore, this study aimed to establish the safety profile of preoperative administration of heparin for thromboprophylaxis in Chinese patients intended for thoracoscopic major thoracic surgery. Methods: From June to August 2016, patients intended for thoracoscopic lobectomy, esophagectomy, and thymectomy were randomly assigned into two groups: the case group (starting heparin sodium 5,000 U, bid preoperatively upon the admission into our department) and the control group (starting heparin sodium 5,000 U, bid postoperatively from postoperative day 1). The baseline data including demographic data and preoperative conditions were collected. The end points included operation time, intraoperative bleeding volume, postoperative chest tube drainage volume and duration as well as lab coagulation function data. Results: A total of 58 qualified patients were randomized into case group (29 patients) and control group (29 patients), and after excluding 6 conversion patients, the case group and control group each had 26 patients for analysis. The baseline data of the two groups were comparable. Operation time (P=0.368), intraoperative bleeding volume (P=0.231), postoperative drainage days (P=0.466), and mean drainage volume per day (P=0.108) were not significantly increased in case group compared with those of control group. Moreover, there were no significant differences of perioperative coagulation function between these two groups. Conclusions: Preoperative administration of heparin for thromboprophylaxis in Chinese patients intended for thoracoscopic major thoracic surgery was safe and feasible. Trial registration: NCT02940444 (https://register.clinicaltrials.gov/).